The impact on mediastinal recurrence based on the number of harvested mediastinal lymph nodes and assessed N2 Stations in patients with stage I invasive lung adenocarcinoma - Chen, Chunji (J Thorac Dis, 2018)
BACKGROUND: To determine the impact of the number of harvested mediastinal lymph nodes (MLNs) and assessed N2 stations on the mediastinal recurrence for pathologic stage I invasive lung adenocarcinoma (IADC). METHODS: A total of 2,048 patients with stage I IADC undergoing surgical resection were enrolled at Shanghai Chest Hospital from 2009 to 2013. Survival analysis was performed by Kaplan-Meier method along with univariable and multivariable cox regression analysis. RESULTS: For patients with ≥5 MLNs, mediastinum-specific relapse-free survival (MS-RFS) rates were 98.3% and 96.6% for 3- and 5-year, respectively, which significantly demonstrated better survival outcomes against those with <5 MLNs (96.3% and 92.8%, respectively, log-rank P=0.018). Additionally, the 3- and 5-year RFS of patients with assessed N2 stations ≥3 (98.2% and 95.8%) were exceptionally better when compared with those with N2 stations <3 (95.5%, 90.3%, log-rank P<0.001). In the univariable and multivariable cox analyses, we found that the number of assessed N2 stations was an independent predictor to MS-RFS (HR =0.468; 95% CI, 0.312–0.867; P=0.020) as opposed to the number of harvested MLNs (HR =0.856; 95% CI, 0.423–1.489; P=0.543) which was not a predictor. CONCLUSIONS: Based on our results, we recommend, for a better MS-RFS among patients with pathological stage I IADC, that the cutoff values for harvested MLNs and assessed N2 stations be 5 and 3, respectively. In addition, the number of assessed N2 stations was still an independent predictor to MS-RFS.